Chronic pain patients' willingness to share personal identifiers on the web for the linkage of medico‐administrative claims and patient‐reported data: The chronic pain treatment cohort. Issue 8 (4th May 2021) - Lacasse, Anaïs; Gagnon, Véronique; Nguena Nguefack, Hermine Lore; Gosselin, Mélissa; Pagé, M. Gabrielle; Blais, Lucie; Guénette, Line
Abstract: Purpose: The linkage between patient‐reported data and medico‐administrative claims is of great interest for epidemiologic research. The goal of this study was to assess the willingness of people living with chronic pain to share personal identifiers on the web for the linkage of medico‐administrative and patient‐reported data. Methods: This methodological investigation was achieved in the context of the implementation of the chronic pain treatment (COPE) cohort. A web‐based recruitment initiative targeting adults living with chronic pain was conducted in the province of Quebec (Canada). Results: A total of 1935 participants completed the questionnaire (mean age: 49.86 ± 13.27; females: 83.69%), 921 (47.60%) of which agreed to data linkage and shared their personal identifiers (name, date of birth, health insurance number online). The most common reasons for refusal were: (1) concerns regarding data security/privacy (25.71%) and (2) the belief that the requested data were too personal/intrusive (13.52%). Some participants did not understand the relevance of data linkage (11.81%). Participants from the COPE cohort and those from the subsample who agreed to data linkage were comparable to other random samples of chronic pain individuals in terms of age and pain characteristics. Conclusions: Although approximately half of the participants refused data linkage, our approach allowed for the implementation of a data platform that contains a diverse and substantial sample. This investigation has also led to the formulation of recommendations for web‐based data linkage, including placing items designed to assess willingness to share personal identifiers at the end of the questionnaire, adding explanatory videos, and using a mixed‐mode questionnaire.